2012
DOI: 10.1051/0004-6361/201118409
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of the hierarchical building-up of the structure on the gas kinematics of galaxies

Abstract: Context. Recent observational and theoretical works have suggested that the Tully-Fisher relation might be generalised to include dispersion-dominated systems by combining the rotation and dispersion velocity in the definition of the kinematical indicator. Mergers and interactions have been pointed out as responsible of driving turbulent and disordered gas kinematics, which could generate TullyFisher relation outliers. Aims. We investigated the gas kinematics of galaxies by using a simulated sample that includ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…As pointed out in Kannappan et al (2002), the dispersion in the TF relation, particularly regarding the dwarf galaxy population, is mainly related to recent perturbations in their evolution, which is consistent with Kassin et al (2007) and de Rossi et al (2012), who argue that the dispersion and residuals correlate with the morphology and kinematical indicators. (2007) to w 50 , assuming a Gaussian shape for the line profile, such that v circ = 1.52 × w 50 /2 (e.g., Gurovich et al 2010).…”
Section: Mass -And Luminosity -Tully-fisher Relationsupporting
confidence: 83%
“…As pointed out in Kannappan et al (2002), the dispersion in the TF relation, particularly regarding the dwarf galaxy population, is mainly related to recent perturbations in their evolution, which is consistent with Kassin et al (2007) and de Rossi et al (2012), who argue that the dispersion and residuals correlate with the morphology and kinematical indicators. (2007) to w 50 , assuming a Gaussian shape for the line profile, such that v circ = 1.52 × w 50 /2 (e.g., Gurovich et al 2010).…”
Section: Mass -And Luminosity -Tully-fisher Relationsupporting
confidence: 83%
“…Recently, Cortese et al (2014 found that early-type galaxies exhibit a T-F relation similar to spirals, although with markedly larger scatter. These findings imply that the T-F relation is a general trend in "regular" rotating systems regardless of galaxy morphology, and if dynamical interactions change the angular momentum of galaxies, they introduce scatter in the T-F relation (Kassin et al 2007;Covington et al 2010;De Rossi et al 2012).…”
Section: Introductionmentioning
confidence: 84%
“…There are other mechanisms that can lead to the formation of an S0 galaxy, for instance internal secular processes such as bars or strong gas outflows and inflows induced by torques and nuclear activity (Laurikainen et al 2009(Laurikainen et al , 2013De Rossi et al 2012). Furthermore, some studies argue that the mechanisms producing S0 galaxies do not mainly depend on the environment, but on the mass of the galaxy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, major mergers can transform spiral galaxies initially obeying the TFR into a remnant typically in an outlier location (e.g. Kauffmann et al 1999;Kronberger et al 2007;Covington et al 2010;De Rossi et al 2012). Covington et al (2010) analysed the location of intermediate and advanced stages of major and minor mergers in the stellar TFR, an analogue of the traditional TFR in which the luminosity is replaced by the stellar mass of the galaxy (log(V rot,max ) -M ⋆ ).…”
Section: Introductionmentioning
confidence: 99%